Avaliação da Citotoxicidade de uma nova pasta obturadora para dentes decíduos - Basso, Ana Luísa (2021)
Objective: This study aimed to evaluate in vitro, the cytotoxicity of a new filling paste for deciduous teeth. Methods: Cytotoxicity was assessed using of the MTT assay. After preparing the cell culture medium, 100 uL of the following solutions were added individually to the wells containing the medium: for ISO 10993, the controls must be inert and the means used in the extraction can be used. In addition of the culture medium (negative control), Guedes-Pinto Paste, Oxide Paste of Zinc and Eugenol, Calen Paste and Experimental Paste, being incubated in the period of time of 1 hour, at a concentration of 50 mg/mL. All experiments were performed in triplicate and cell viability percentages were calculated in with respect to cellular controls. Data were analyzed using the one-way test ANOVA followed by Tukey's post-hoc (α=0.05). Results: The highest rate of cell viability was observed in the control groups, Pasta Guedes-Pinto and Pasta Experimental, being statistically different from the other groups (p<0.05), without statistically significant difference between them (p>0.05). Conclusion: It was possible to conclude that the Experimental Paste showed no cytotoxicity.